The Characteristics of Mosque Architecture Based on Public Preferences in Malang City - Wulan Astrini; E B Kurniawan; M Abdillah (Diponegoro University, 2020)
Mosque is an architectural work and public facility that serves as a worship place for Muslims. Mosque architectural elements include domes (roofs), mihrab, minaret, arch, and ornaments. Mosque architecture comprises of various elements, which adapt to the local culture where the mosque is located. As such, its presence also bears some impacts on the appearance of urban architecture. Malang city as one of the major cities in East Java has numerous rapidly developing mosque architectures, including Jami’ Great Mosque of Malang, Sabilillah Mosque, Nurul Muttaqin Mosque, Ahmad Yani Mosque, and Manarul Huda Mosque. The meaning of architectural work is also closely related to the perception of humans who observe it. The public preference for the architectural characteristics of mosques in Malang city is a manifestation of architectural work. Conjoined analysis is employed as method operative to analyze public preference. This study aims to find out the architectural characteristics of mosques in Malang city according to public preferences. The findings can serve as a recommendation for the development of mosque architectural designs in Malang city, especially those possessing locality values. The architectural characteristics of mosques in Malang city which are driven by the public preferences ranging from the highest to the lowest, which is why mosques generally have calligraphy ornaments, circular arch, pentagon-shaped minaret, Indo-Persian dome, and two-minaret design.